النموذج السببي للعلاقة بين الإعزاءات السببية والتفكير الخرافي وجودة الحياة لدى طلاب الجامعة - الحديبي، مصطفى عبدالمحسن عبدالتواب; عبدالمجيد، نهلة عبدالرزاق (جامعة الملك فيصل, 2020)
يؤثر التفكير الخرافي على المجتمع بشكل سلبي، وقد هدفت الدراسة الحالية إلى الكشف عن الفروق بين متوسطات درجات طلاب الجامعة طبقا لمستويات التفكير الخرافي الثلاثة (منخفض، متوسط، مرتفع) في الإعزاءات السببية وجودة الحياة، والكشف عن الفرق بين متوسطي درجات طلاب الجامعة في التفكير الخرافي طبقا للنوع، والتخصص الدراسي، ومنطقة السكن، والفرقة الدراسية، والتحقق من صحة النموذج الإحصائي المقترح بين الإعزاءات السببية والتفكير الخرافي وجودة الحياة لدى طلاب الجامعة؛ للتوصل إلى نموذج يحدد الآثار المباشرة وغير المباشرة بين التفكير الخرافي وتلك المتغيرات في ضوء ما تعكسه بيانات الدراسة، وبلغ عدد أفراد الدراسة الاستطلاعية (189) طالبا وطالبة، في حين بلغ عدد أفراد الدراسة الأساسية (716) طالبا وطالبة من كلية التربية جامعة أسيوط، طبق عليهم مقياس التفكير الخرافي، ومقياس الإعزاءات السببية لطلاب الجامعة (إعداد الباحثين)، ومقياس جودة الحياة لطلاب الجامعة إعداد منسي وكاظم سنة 2010. أسفرت نتائج الدراسة عن وجود فرق دال إحصائيا بين متوسطي درجات مستويات التفكير الخرافي الثلاثة على مقياسي الإعزاءات السببية وجودة الحياة لطلاب الجامعة وأبعادهما الفرعية في اتجاه مرتفعي التفكير الخرافي، ووجود فروق في التفكير الخرافي ككل وأبعاده الست تعزى لبعض المتغيرات الديموجرافية المتمثلة في: التخصص الدراسي، والفرقة الدراسية وذلك في اتجاه طلاب الشعب الأدبية، والفرقة الأولى، في حين لم توجد فروق تعزى للنوع، ومنطقة السكن، كما أظهرت نتائج تحليل المسار مؤشرات حسن مطابقة للنموذج المقترح؛ وبتحليل التوسط لنموذج المعادلة البنائية النهائي بطريقة توليد العينات المتتالي اتضح أن متغير الإعزاءات السببية يتوسط العلاقة بين التفكير الخرافي وجودة الحياة لدى طلاب الجامعة.
Superstitious thinking had negative effects on societies. This study aimed to investigate the university students' differences of superstitious thinking levels (low, medium, or high) for both causal attributions and life quality for with its three levels in addition to detect the differences due to gender, specialization , place of living and class of study. The work also aims to verify the validity of the proposed statistical model of causal attributions, supersti-tious thinking, and life quality of university students so that the model better determines direct and indirect effects between the superstitious thinking and those variables based on what the study data reflect. The sample of the pilot study included 189 students whereas the main study sample included 715 students enrolled in the college of Education, Assiut University. The study tools were Superstitious Thinking Scale (STS), Causal Attributions Scale (CAS), and Quality of Life Scale (QOLS) for university students. Results showed a statistically significant difference between the means of the three level scores of STS on both CAS and QOLS and their dimensions for university students in favor of students with high-level superstitious thinking. Results also revealed statistically significant differences in STS and its dimensions due to some demo-graphic variables including specialization and class of study in favor of students in literary-study sections and first year students. On the other hand, there were no differences in STS due to gender and neighborhood. Additionally, path analysis asserted the proposed model validity. Finally, through mediation analysis of the constructive equation model, it was concluded that causal attributions is a mediator variable between superstitious thinking and quality of life for university students.
Keywords: علم النفس الإيجابي -- طلاب الجامعات -- العزو السببي -- الرضا عن الحياة -- الصحة النفسية